Kondisi Biosekuriti Tempat Penjualan Burung Terkait Avian Influenza di Wilayah Jakarta - Ardilasunu Wicaksono; Etih Sudarnika; Chaerul Basri (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
The aims of this study were to identify biosecurity condition and to analyse the relation of bird vendors characteristics toward biosecurity practices and biosecurity condition related to Avian influenza in Jakarta bird markets. Data were collected from four bird markets in Jakarta using randomly interview method of 75 respondents and observe the biosecurity practices in bird markets. Data were analysed using chi-square test and gamma test to analyse the relation between bird vendors’ characteristics and biosecurity condition. The result showed that 69,3% of bird vendors did the biosecurity practice in moderate level and only 10,7% did it well, meanwhile, most of bird kiosks (53,5%) in Jakarta got the poor category of biosecurity level. Beside that, bird vendors’ characteristics which has the significant relation (p<0,05) were age (p=0,003), education level (p=0,007), training (p=0,047), knowledge (p=0,000) and attitude (p=0,000) toward biosecurity condition related to Avian influenza in Jakarta bird markets.